2008
DOI: 10.1111/j.1440-1843.2008.01393.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrofluoroalkane–ethanol inhalers on estimated alcohol levels in asthmatic subjects

Abstract: BEC are transiently elevated after inhalation of HFA-ethanol MDI; however, by 5 min, BEC had already returned to baseline levels. Thus the effect of HFA-ethanol MDI on BEC is transient and would be negligible after 5 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Consequently, if BAC was checked at a workplace with zero tolerance for alcohol, the employee could potentially be subject to negative actions by the employer. Our results are consistent with prior studies 1,2 in that there is rapid decline in breath ethanol levels. While it is unlikely that BAC would be checked within 1 min of using the MDI, it is possible in that some patients who are short of breath will use poor technique described above and be tested randomly, with no knowledge of the potential for a false-positive result.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Consequently, if BAC was checked at a workplace with zero tolerance for alcohol, the employee could potentially be subject to negative actions by the employer. Our results are consistent with prior studies 1,2 in that there is rapid decline in breath ethanol levels. While it is unlikely that BAC would be checked within 1 min of using the MDI, it is possible in that some patients who are short of breath will use poor technique described above and be tested randomly, with no knowledge of the potential for a false-positive result.…”
supporting
confidence: 93%
“…Bruce et al 1 and others 2 have reported metered-dose inhalers (MDI) that contain ethanol cause false-positive 'breathalyser' tests.…”
Section: False-positive Breathalyser Tests and Use Of Metered-dose Inmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter risk was recently reported to increase by 25% for each 1000 mcg/day increase in the dose of beclometasone or equivalent 61 . One potential ‘side‐effect’ that is not well known is that some non‐chlorofluorocarbon(CFC) inhalers contain alcohol, which can transiently (for <5 min) increase breath ethanol concentration; 62 this may be relevant in some cultures or in countries where random breath testing is performed for road safety reasons.…”
Section: Asthma—clinicalmentioning
confidence: 99%